DETERMINANTS OF PREFERANCE OF HOMEOPATHICF TO ALLOPATHIC TREATMENT - Aymen Naeem (Baqai Journal of Health Sciences)
Homeopathy is considered as the most widely practiced and safe alternative form of medical treatment such as allopathic medicine. It was introduced by a German doctor who believed that minimum dose of a drug can alleviate the symptoms similar to other conventional forms of treatment. The objective of the present study was to determine the factors that influence individuals attitude towards homeopathic treatment. A cross-sectional descriptive study was conducted in different homeopathic clinics of Bhawalpur from January 1 to February 1, 2017. A total of 72 patients (both genders) were included in the study by using convenient sampling technique. A pretested questionnaire containing personal information and subject related questions was used to collect the data. The questions were interviewed from the patients in the local language and were transferred to the questionnaire in English. The study concluded that 87% of the respondents preferred homeopathic treatment while around 13% favored the use of allopathic medicines. The reasons for high utilization of homeopathic medicines can be attributed to the high efficacy, low cost, better taste, minimum side effects and forefathers trend.